Identifikasi Supervisi dan Monitoring pada Penyelenggaraan Paket A di PKBM Teratai Kota Cilegon - Rahmawati, Indi; Cecilia, Putri; Hayati, Fatihah Nurul; Wahyuni, Nabilla Putri (Eastasouth Journal of Positive Community Services, 2023)
Abstract: The purpose of this research is to describe the form of PLS supervision and monitoring activities in PKBM Teratai. This research is a descriptive qualitative research by collecting data through interviews and observations which were carried out in April 2023 in Cilegon, Banten. The results of data analysis in this study stated that the problems in PKBM Teratai included obstacles from the learning residents themselves such as a lack of awareness of learning, the limited number of infrastructure facilities, and after monitoring some of the learning residents experienced learning trauma so that the need for counseling personnel such as counseling guidance so that learning citizens can develop themselves according to their potential. The results of this monitoring evaluation can be seen from the planning of learning programs, the implementation of learning activities including implementation constraints, achievement of learning program indicators, administration of study groups, best practices during program implementation, serious problems to their resolution steps.